Hypothesis and Verification For The Existence of Self-Propelled Energy Sources for Covid-19 Virus - Zheng Chao; Shi Yue-Jin (International Journal For Research In Biology & Pharmacy, 2024)
This is a follow-up paper from a published one "New discoveries in technology to disinfect living COVID-19 viruses from the inside Human Cells, (International Journal For Research In Medical Physics, Issue-4 | April, 2023"). In the first paper, it has listed some important breakthroughs in the areas of fighting against COVID-19 virus spread . In today's paper, more technical details are disclosed regarding those breakthroughs. The primary focus of this paper is to elaborate some of the major components of this technical breakthroughs. The first is related “Electronic Communication Technology (ECT)” to the an establishment between a “Direct Electronic Communication Channels” (DECC) between human and the“Covid-19 Virus Energy System (CVES)”. All these would be brand new discoveries with which no prior instances have been identified and each of them will certainly causing changes in the paradigm of school of thoughts, and plus the associated technologies and the methodologies along with. By any means, one major technical breakthroughs we cannot go without mentioned. This finding is related to the fact that Covid-19 Virus Energy System (CVES) was born with its own “Open” & “Shut Down” control system. In the last 3 4 years, this finding has served as the foundation for MMC-C19 Plasters, a specialized anti-Covid-19 Virus spread product developed by the Team. The product have been approved by Thailand MOH in July 2022, and also it is full of the ideology of “Medical Physics” in mind and equally full of market effectiveness after its proper used.